Zapomenutá skica Josefa Šercla „Čechoslováci v Bulharsku“ (1950) - Jakoubek, Marek (Lidé města, 2019)
The main body of the contribution represents the document (currently deposited in the archives of the “T. G. Masaryk” Czechoslovak Club in Sofia) “Czechs and Slovaks in Bulgaria”, written by the president of the “T. G. Masaryk” Czechoslovak National House in Sofia, Josef Šercl. Šercl’s text offers historically oriented and complex information about the Czechs and Slovaks in Bulgaria, which makes it an important source for the study of the history of their presence in the country. The text is preceded by a short outline of Czech academic interest in Bulgaria and a short biographical note on Josef Šercl.